PROTECTION OF INDONESIAN MIGRANT WORKERS FROM INTERNATIONAL CRIME SYNDICATES THROUGH THE MARITIME CONTROL SYSTEM - Aminullah, Faujan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Maritime Security is a crucial element in maintaining national sovereignty and stability. Indonesia, as the largest archipelagic country in the world, faces significant challenges in securing its maritime territory, particularly from the threat of international crime syndicates through illegal migrant workers. These syndicates exploit migrant workers who are not registered with the government, causing them to become involved in transnational crimes as proxies for criminal syndicates. Indonesia's strategic position at the crossroads of international trade and migration routes makes it a prime target for these criminal activities. The less stringent monitoring of Indonesian citizens compared to foreign nationals further complicates prevention and countermeasures. International crime syndicates utilize illegal migrant workers to carry out various criminal activities such as terrorism, drug trafficking, and money laundering. These activities not only threaten national sovereignty and security but also damage Indonesia's reputation as a country that upholds human values and human rights. Therefore, addressing the threat from international crime syndicates through illegal migrant workers must be a top priority. The Indonesian government needs to undertake integrated efforts involving various agencies such as Ministries, the Navy, the Maritime Security Agency, the police, as well as international bodies and non-governmental organizations focused on human rights. Public participation and increased public awareness are also crucial in ensuring national security and sovereignty. The development of effective strategies and policies to prevent, detect, and address these illegal activities is essential to maintain Indonesia's national sovereignty and integrity.Keywords: Maritime Security, Illegal Migrant Workers, International Crime Syndicates